Effects of egg washing and storage temperature on the quality of eggshell cuticle and eggs - Liu, Yu-Chi; Chen, Ter-Hsin; Wu, Ying-Chen; Lee, Yi-Chain; Tan, Fa-Jui (Food chemistry, 2016)
•Egg quality deteriorated gradually with increasing storage temperature and time.•Storage temperature more prominently influenced egg quality.•Egg washing reduced cuticle coverage.•Various techniques were used to analyze the quality of cuticle.•High correlations were observed between the quality parameters evaluated. This study investigated the quality of washed and unwashed eggs stored at 7°C (WC and UC for washed and unwashed eggs, respectively) and 25°C (WR and UR for washed and unwashed eggs, respectively) for 4weeks. The results show that the Haugh unit, albumin pH, thick albumin ratio, yolk index, air cell size, and S-ovalbumin content of UC were significantly the most superior, followed by those of WC, WR, and UR, in that order. Scanning electron microscopy and cuticle staining confirmed the damages and decreased cuticle coverage caused by washing and extended storage. Attenuated total reflection Fourier transform infrared spectroscopy revealed that cuticle composition changed significantly after washing and storage (P<0.05). High correlations were observed between the quality parameters evaluated. In conclusion, storage temperature critically influenced egg quality, and egg washing reduced cuticle coverage.